Instructional leadership as a catalyst for organizational commitment: insights from a systematic literature review - Othman, Cammellia; Busari, Abdul Halim (Institute of Advanced Engineering and Science, 2025)
This research intends to provide insight on the relationship between instructional leadership and organizational commitment, with a specific emphasis on the timeframe spanning from 2009 to 2023. Using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) approach, this study conducted a systematic search of academic databases, including Web of Science (WoS), Scopus, and ERIC. The search produced a large selection of papers, reviews, and articles about organizational commitment and instructional leadership. The analysis demonstrated the critical role that the impact of instructional leadership on organizational commitment played by using an advanced search strategy involving keywords, such as “instructional leadership,” “educational leadership,” “school leadership,” “organizational commitment,” “employee commitment,” and “workplace commitment.” The review identified three main themes from the final dataset, which included 33 items. These themes were: i) instructional leadership and teachers; ii) organizational commitment and school leadership styles; and iii) leadership in diverse educational contexts. The key themes were then validated by experts. The analysis reveals school leaders’ potential contributions to organizational commitment, which has consequences for educational leadership and management.